Evaluación de la densidad de plantas, componentes fenológicos de producción y rendimiento de granos en diferentes materiales genéticos de maíz - Martínez Uribe, Raúl Andrés [UNESP]; Kölln, Oriel Tiago; de Castro Gava, Glauber José (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2017)
The aim of this study was to verify the influence of planting distance and the population of plants, phenological components, and productivity in different maize genetic material. The experiment was conducted during the 2003/04 agricultural year in the city of Jaú/SP, located at latitude 22º 17‘S, longitude 48º 34’ W and altitude 680 m. Average Were studied, planting distances of 0.45 m and 0.90 m, three densities 50, 75 and 100 000 plants ha–1, and four genetic materials: simple hybrid DKB 333C, triple hybrid DKB 466, AG 2060 and double hybrid the variety AL 2x3x4 factorial scheme Bandeirantes in with 4 replications in randomized blocks. The reduction in the planting row spacing and increasing plant population significantly influenced the percentage of lodged plants and broken corn. Line spacing of 0.45 m, population of 75,000 plants ha–1 and single hybrid material showed the highest productivity of grains with an average of 9077 kg ha–1. Significant interactions were observed line spacing factors versus population of plants and plant population versus materials for grain productivity factor. Phonological components of production: spike length, shank diameter and the diameter of the cobs were influenced by increased plant population ha–1. The experiment was conducted during the agricultural year of 2003/04 in the city of Jaú/SP, located at latitude 22º 17’S and longitude 48º 34’W and an average altitude of 680 m. Were tested, two spacing 0.45 m and 0.90 m, three densities 50, 75 and 100 thousand plants ha–1, and four genetic materials simple hybrid DKB 333C, triple hybrid DKB 466, double hybrid and variety AG 2060 in AL Bandeirantes® factorial design 2x3x4 with 4 replications in randomized blocks.
Evaluation of plant density, phenological components of production and grain yield in different corn genotypes
Keywords: Hybrids; Plant population; Zea mays